Prospects of the development of internet marketing as a unique tool for the promotion of the product - Bohdanov, Serhii (Management and Entrepreneurship: Trends of Development, 2017)
The relevance of the topic is predetermined by the dynamic growth of the Internet marketing sector, which is rapidly progressing. In modern conditions of the spread of communications and information technologies the importance and expediency of using its potential cannot be overemphasized.Purpose. The goal is to study the development of the database and tools for promoting the product in the worldwide Internet.Design/methodology/approach. The basic principles of research are analytical, systemic and comparative methods, information and axiological approaches have been used.Findings. The subject of the study are analytical and applied aspects of the development of marketing tools. The Internet marketing facilities and tools are considered as the essential components of marketing activities of almost any enterprise, aspiring to work effectively in the domestic and international market. Therefore, the need of qualitative projection and usage of Internet marketing facilities and tools is justified. Analysis of the development of Internet marketing technologies and the dynamics of their spreading allows to make a forecast, according to which this type of marketing will become dominant over the next decade due to the progressive growth of its application areas.Research limitations/implications. The paper clearly substantiates the role of Internet marketing as an integral tool that directly affects the competitiveness of the enterprise and the results of its activities.Originality/value. The scientific significance of the work is manifested in the research of the issues of global information network usage and the development of such activity in the aspect of the development of the information sphere in the world as a whole